The Students’ Attitude Toward Reading E-Books at SMA Istiqamah Muhammadiyah Samarinda - Ade Ismail Ramadhan Hamid; Lisha Amelia (Universitas Muhammadiyah Kalimantan Timur, 2023)
This study aimed to determine students' attitudes toward reading electronic books at school. The population of this study was students at SMA Istiqamah Muhammadiyah Samarinda in academic 2022/2023 with a total population of 132 students. The sample of this study was made up of 11th-grade students using the purposive sampling technique; 21 students were selected as the sample of this study. The descriptive-quantitative approach is used in this study, with students accessing an English e-book website. The instrument employed in this study was a questionnaire to determine the attitudes acquired. The data in this study was analyzed using quantitative data analysis techniques. The results showed that students’ attitudes toward reading e-books were positive.